VACTERL association – Ultrasound findings and autopsy correlation - Gaur, Naman Kumar; Gokhale, Sudheer (Indian Journal of Radiology and Imaging, 2018)
VACTERL (vertebral, anal, cardiac, tracheoesophagus, renal, and limbs) is an abbreviation for the congenital group of abnormalities, including vertebral or vascular anomalies, anal atresia, cardiac defects, tracheoesophageal – fistula/esophageal atresia, renal defects, and limbs defects. It is a rare association and not accidental event where several organs are affected by developmental defects during blastogenesis. The exact cause is unknown; however, several environmental and genetic factors are included in literature. Three components out of seven are used to label as VACTERL. The combination is necessary, but the patient may have other congenital malformations as well. We present here an antenatal scan with autopsy correlation of one of the forms of VACTERL association spectrum.
Keywords: Diagnosis of exclusion; VATER; vertebral, anal, cardiac, tracheoesophagus, renal, and limbs